The Differences Analysis of Temperature, Salinity, and Dissolved Oxygen of Aedes aegypti Breeding Place Water in Endemic and Non-Endemic Areas - Nurul Hidayah; Dwi Rahmawati (Fakultas Kedokteran Universitas Lambung Mangkurat, 2019)
Abstract: The study aims to determine differences in water quality of breeding sites in endemic and non-endemic areas. The method used is quantitative observational analytic with a case control study design. Case group was water parameters in endemic areas and the control group is in non-endemic areas. 43 samples of breeding water were taken from each area then water quality measurements were carried out. Data were analyzed using independent t-test. The results obtained mean temperature in endemic areas 27.51 ± 0.739 oC, salinity 2,544 ± 0.638 gr/l, and DO 7,253 ± 1,097 mg/l. The mean temperature in non-endemic areas is 25.7 ± 1.124 oC, salinity is 2.472 ± 2.365 gr/l, and DO is 6.479 ± 1.059 mg/l. P-value of statistical tests of differences in temperature, salinity, and DO parameters in endemic and non-endemic areas are 0.000, 0.266, and 0.001. It was concluded that temperature and DO parameters in endemic areas proved to be significantly different from those in non-endemic areas. However, for salinity variables there are no significant differences. Keywords: Aedes aegypti, dissolved oxygen, salinity, temperature